II. MEŞRUTİYET SONRASINDA ÇIKAN KISA ÖMÜRLÜ BİR GAZETE: BOSNA - Aydın, Ahmet (Bartın Üniversitesi, 2015)
Osmanlı Devleti'ndeki basın hayatı incelendiğinde, II. Meşrutiyet'in (24 Temmuz 1908) çok önemli bir konuma sahip olduğu görülecektir. Çünkü bu olay basın hayatına yeni bir soluk getirmiş, birçok yayın organı bu olaydan sonra gün yüzüne çıkmaya başlamıştır. İşte bu dönemde yayın hayatına başlayan ve çok kısa bir süre hayatta kalan bir gazeteyi tanıtacağız: Bosna Gazetesi. Bu gazete, 31 Ekim ve 7 Kasım 1908 tarihlerinde iki sayı olarak çıkmıştır. İmtiyaz sahibi ve başyazarı Bosnalı Mehmed Nureddin olan gazete, İstanbul'da basılmış ve tamamı Osmanlıcadır. Bu çalışmada Bosna Gazetesi'ni tanıyacak ve onun gözüyle Osmanlı'yı ve Balkanları inceleyeceğiz.

When examined the press life of the Ottoman Empire, II. Constitution Period (24 July 1908) is viewed as having a very important position. Because, in this incident has brought a new lease of press life, many publications began to emerge the day after this incident,. Here, we will examine a newspaper which began its press life in this period but lasted a very short duration: Newspaper of Bosna. This newspaper is a which published as two numbers in 31 October and 7 November 1908. Publisher and editor of the newspaper is Bosnian Mehmed Nureddin, it was printed in Istanbul and the publication language was Ottoman Turkish. In this study, we will introduce the ' Newspaper of Bosna and examine the Ottoman and the Balkans through his eyes.
SHORT?LIVED A NEWSPAPER OF AFTER THE SECOND CONSTITUTION PERIOD: BOSNA